Make this easy from the beginning by multiplying through by 12. Look,
(12)(1/3)x + 12(1/4) = (12) x - (12)(1/6)
4x + 3 = 12x - 2
Now we put the x's on one side, the constants on the other. That's subtract 12 x from both sides, and subtract 3 from both sides.
-8x = -5 now divide by -8
x = 5/8 (note how the negatives cancelled each other)
umm if x=1/6 then do 1/3 x 1/6 + 1/4 thne see wat u get !
is it 1/3x or (1/3)x..since u mentioned abt denominator being 12.i assume it to be one-third of x.
then we get (4x+3)/12= (12x-2)/12
we can get rid of 12 on both sides
therefore we have 4x+3 = 12x - 2
therefore 12x - 4x = 3+2
8x = 5.
and for u to not feel guilty i leave it here.but wht surprises me is u figured out to take the common denominator and u couldnt solve it..when the hardest part of the prob is that step.
put the x's on one side and the constants on the other, which would give you:
simplify both sides, and you would get:
multiply both sides by (3/2), which would be dividing by (2/3)
that would give you x=(5/8)
sorry i gave you the answer, but i hope this helped, i explained it so that you can figure out similar questions.
This article contents is post by this website user, EduQnA.com doesn't promise its accuracy.
More Questions & Answers...